One Step Process of Producing Reduced Graphene Oxide from Silantek Sub-Bituminous Coal Using Microwave Irradiation Heating - N.Iqbaldin, M.; I. Azlan, M.; Khudzir, I. (International Journal of Engineering and Technology, 2018)
Reduced graphene oxide (rGO) was prepared from purified Silantek sub-bituminous coal by using microwave irradiation heating with the presence of FeCl3 and ZnCl2 as graphitizing and activating agents, respectively. The preparation was carried out at microwave power level ranging from 600 to 1000W. The results showed that rGO produced from sub-bituminous coal has same characteristics as produced from graphite. X-ray Diffraction (XRD) spectra showed that theÂ  sharp peak presence at 2Î¸ = 26Âº had decreased and broaden after microwave irradiation heating due to the removal of various oxide groups with interlayer distance reduced to 0.337nm similar to that of graphite. Further, Raman spectra showed a high degree graphitization of rGO produced at 900 and 1000W of microwave irradiation power level. Moreover, the degree of crystallinity of rGO produced from coal is 1.31 (G900) and 1.15 (G1000), which is similar to rGO produced from graphite. Thus, this suggest that purified Silantek sub-bituminous coal upon heating using microwave irradiation method is potentially to be used as a carbon precursor to produce rGO.Â